Gestalt Communication: An Intelligent Approach that Enhances our Humanity in Pursuit of Sustainability (Ágora de Heterodoxias, 2025)
The human being as a historical social being is a being in relation to others, that is to say, the human being is sustained in the episteme in which our being and doing develops, and occurs in the communicative relationship with others and with ourselves. From this premise, the social action that is preceded by the communicative act may or may not make it possible to proactively address the challenges that imply the adoption of dynamic adjustments to enhance the achievement of our way of facing the challenges of sustainable development demanded by the social historical context, or to get ahead of them in a proactive and prospective manner. One may ask how the process proposed by the Sustainable Development Goals (SDGs) issued by the United Nations in 2015, which define seventeen specific goals to be achieved by the year 2030
Keywords: Gestalt Communication; Sustainable Development Goals (SDGs); Smart Communication; United Nations